Restructuring and Regulatory Reform in the Power Sector: Review of Experience and Issues - Peter Choynowski (Asian Development Bank (ADB), 2004)
A worldwide trend began in the 1980s in both developed and developing countries to restructure their power sectors and reform their regulatory framework. The motivation in developed countries to restructure and reform was mainly to improve sector efficiency, while in the developing countries, it was to move the sector away from reliance on scarce public resources to more private sector financing. Since the Asian Development Bank was involved in restructuring and regulatory reform in many of Asia's developing countries, this paper attempts to take stock of the progress made to date in these countries, review the relevant experience in some developed countries and Latin America, and identify the key issues that could have a bearing on its operations in Asia.
hdl:11540/1909
Keywords: 330; Elektrizitätswirtschaft; Elektrizitätspolitik; Regulierung; Privatisierung; Lateinamerika; Industrieländer